More than just good grades: candidates’ perceptions about the skills and attributes employers seek in new graduates - Velasco, Manuel Salas (Journal of Business Economics and Management, 2012)
There is a common belief among university students that they have to study hard attempting to earn high grades because employers are targeting graduates with outstanding academic records. However, this idea does not seem to capture what is actually happening in organizations, as firms value more aspects related with personality and other personal qualities of young graduates. We present a case study of the hiring process of recent university graduates to test these hypotheses. The methodology used follows a two stage approach. Principal component analysis allows us to identify first key categories of skills and attributes that influence the selection process. Then, using econometric analysis, a matrix classifies them according to employer size and type, degree, position and industry. The results show that soft skills (personality and other qualities) are the most required attributes in the selection process. Good academic records only matter in the public sector.